Industrial organisation : competition, growth, and structural change - George, Kenneth Desmond (Routledge, 1992)
As most economies remain caught in a global recession, that shows little sign of abatement, the importance of maintaining a flourishing industrial sector for the economic wellbeing of a country has rarely been so relevant. Industrial Organisation has long served as a basic introduction to this subject. The book is concerned with economic problems and policy issues that arise from the activities of firms. The authors reject the traditional micro-economic analysis of market structure in favour of studying conduct and performance in the context of macro-economic policy and the environ.
Keywords: Industrial organization (Economic theory); Industries -- Great Britain.; Industries -- European Economic Community countries.; Industries -- United States.; Économie industrielle.; Industrie -- Grande-Bretagne.; Industrie -- Pays de l'Union européenne.; Industrie -- États-Unis.; BUSINESS & ECONOMICS -- Infrastructure.; BUSINESS & ECONOMICS -- Corporate & Business History.; Industries; European Economic Community countries; Great Britain; United States; Business -- Economics